MINGLE GAME IMPLEMENTATION ON STUDENTS’ VOCABULARY MASTERY - Gabby Maureen Pricilia; Habib Rahmansyah (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Students’ vocabulary mastery is the problem in this research. One of the factor caused the problem is teaching strategy used in teaching vocabulary. This research has purposes to find out: 1) How mingle game implemented in teaching vocabulary, 2) Students’ vocabulary mastery before and after taught by Mingle Game, 3) a significant effect on vocabulary mastery by implementing Mingle Game. The research method was quantitative. The population was 62 students then sample was 31 students who was taken by systematic sampling technique. Observation sheet and test were used as the instruments of this research. The result of research got the implementation of mingle game is very good. Students’ vocabulary before taught by mingle game was fail, and after taught by mingle game was enough. Then, hypothesis testing showed that ttest was higher than ttable , so it clearly determines a significant effect on vocabulary mastery by implementing mingle game.